2016
DOI: 10.1159/000446291
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy Using an Individual 3-Dimensionally Printed Surgical Guide

Abstract: Percutaneous nephrolithotomy (PNL) is an endoscopic technique used for treating large stones, multiple stones, and staghorn calculi. Although minimally invasive, complication rate of PNL reaches 25%, and it is partially associated with needle puncture during nephrostomy tract preparation. Continuous improvement of armamentarium and imaging methods and the introduction of three-dimensional (3D) visualizations optimize the procedure; however, the rapid and precise establishment of the nephrostomy tract is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…When gaining access, we attempted to enter as laterally as possible because the pleura is located more inferiorly at the mid-scapular line. In a recent study, PCNL was performed using an individual 3-dimensionally printed surgical guide that can decrease the initial access time and decrease the complication rate [24]. After a deep inhalation, we determined the location of the desired calyx.…”
Section: Discussionmentioning
confidence: 99%
“…When gaining access, we attempted to enter as laterally as possible because the pleura is located more inferiorly at the mid-scapular line. In a recent study, PCNL was performed using an individual 3-dimensionally printed surgical guide that can decrease the initial access time and decrease the complication rate [24]. After a deep inhalation, we determined the location of the desired calyx.…”
Section: Discussionmentioning
confidence: 99%
“…We also attempted to quantitatively measure the time required to process the radiological images. However, unfortunately, only 4 teams have indicated the details on the duration of their image postprocessing step: Golab et al, 2h; Wake et al, 7h; Gershman et al, 8 to 12h [24,25,32]. Sampogna et al have demonstrated that their first models required multiple hours which was reduced to less than an hour with the experience gained [27].…”
Section: Nephrology Schoolmentioning
confidence: 99%
“…Школа нефролога Likewise, we divided the CAD software pool into 2 groups, commercial and free, and open-source. Only 10 teams have reported their use of CAD software in their 3D printing workflow [15,[24][25][26][27][28][29][30][31][32]. Fig.…”
mentioning
confidence: 99%
“…The ultimate goal is complete stone clearance with lower complication rates, and with the growing market of low-cost 3D printers, PNL procedure can be shortened and the complication associated with needle puncture can be decreased in a cost-efficient manner. [8,9] The prompt evaluation of urological organs is mandatory in traumas. As Peng et al suggested, the enhanced multi -scan CT permits reliable detection of renal trauma and the associated organ or tissue injuries and provide important clinical value for the diagnosis and classification of trauma or internal organ injures, however 3D technology precisely will give guide the surgical decision making process concerning both blunt and penetrating traumas.…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%